Successful Strategies Utilized by “Senat Taruna Kabinet Komando I” at Jakarta Technical University of Fisheries - Angkasa Putra; Sarifah Aini (Jurnal Integrasi Sumber Daya Manusia, 2023)
“Kabinet Komando I” is the designation of the “Senat Taruna” organization at Jakarta Technical University of Fisheries for the 2018-2019 period. This university, operating under the Ministry of Marine Affairs and Fisheries in Indonesia, offers both applied undergraduate and graduate programs. This study aimed to analyze the strategies implemented by the “Kabinet Komando I” to achieve program success. Utilizing a qualitative case study approach, we explored tacit knowledge from its President, who also held the position of Commander of Battalion 07 Barracuda. The research identified five key strategies that contributed to the cabinet’s effective performance: formation of a cohesive team, high and adaptable motivation, effective communication, collaborative efforts, and sound financial management. Additionally, insights from the President emphasized the qualities of visionary, qualified, and intellectual students, echoing the motto that guided their journey: “One Command and One Perception.” This study offers valuable insights into the strategic decision-making processes within the organization following the leadership of “Senat Taruna Kabinet Komando I.”